1997
DOI: 10.1523/jneurosci.17-21-08391.1997
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin-Induced Collapse of Rat Pheochromocytoma (PC12) Cell Growth Cones: A Role for Tyrosine Kinase Activity

Abstract: Pathfinding of growing nerve processes is guided by extracellular guidance cues. Here we report growth cone collapse of NGF-differentiated PC12 cells in culture evoked by the neuropeptide bradykinin. The growth cone response is mediated by B 2 bradykinin receptors. Two different effects were distinguished.(1) Disappearance of filopodia occurred together with a loss of fibrillar actin (F-actin) in the growth cones at picomolar concentrations of bradykinin. The relative F-actin content was measured by means of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…These are similar to the modi®cations of Src occurring upon activation of the PDGF receptor (Ralston and Bishop, 1985), which reportedly re¯ect phosphorylation of residues in the amino terminus of Src and increased Src kinase activity (Gould and Hunter, 1988;Stover et al, 1996). Interestingly, Src activity has been associated with changes in cytoskeletal organization (Thomas et al, 1995;Parsons and Parsons, 1997;Brunton et al, 1997), such as those that might occur during the migration of cells (Hall et al, 1996;Boyer et al, 1997) and the retraction of neurites (Schindelholz et al, 1997).…”
Section: Discussionmentioning
confidence: 53%
“…These are similar to the modi®cations of Src occurring upon activation of the PDGF receptor (Ralston and Bishop, 1985), which reportedly re¯ect phosphorylation of residues in the amino terminus of Src and increased Src kinase activity (Gould and Hunter, 1988;Stover et al, 1996). Interestingly, Src activity has been associated with changes in cytoskeletal organization (Thomas et al, 1995;Parsons and Parsons, 1997;Brunton et al, 1997), such as those that might occur during the migration of cells (Hall et al, 1996;Boyer et al, 1997) and the retraction of neurites (Schindelholz et al, 1997).…”
Section: Discussionmentioning
confidence: 53%
“…8, B and C). Bradykinin, a neuropeptide activating the G proteincoupled receptor and producing intracellular Ca 2ϩ increase, induces neurite retraction (43). We found that bradykinin also induces the tyrosine phosphorylation of RAFTK and paxillin in a Ca 2ϩ -dependent manner in differentiated PC12 cells.…”
Section: Adhesion and Cytoskeletal Organization Through P130mentioning
confidence: 69%
“…It is well documented that BK receptors signal IP 3 Ca 2+ pools, and thus, BK could serve as a stimulus for neuronal growth. In support of this possibility are the observations that BK can cause neurite extension via IP 3 ‐sensitive Ca 2+ signalling upon activation of B 2 receptors in pheochromocytoma (PC12) cells (Kozlowski et al 1989; Reber & Schindelholz, 1996; Schindelholz & Reber, 1997).…”
Section: Discussionmentioning
confidence: 90%